Audit as political struggle: the doxa of managerialism clashing with the uncertainty of real life. Issue 3 (3rd April 2021) - Crewe, Emma; Mowles, Chris
ABSTRACT: Auditing firms tend to promote rule-bound orthodoxies about management based on the fiction that the world is more predictable than it is. Managers in INGOs find that long-term planning requires endless readjustment. This article explores what happens when these conflicting knowledge regimes clash during auditing. It draws on Bourdieu's ideas to illuminate how different forms of social capital come into play in conflicting versions of management and control, whether centralised and prereflected or distributed and adaptive. In this case, a conflict during audit was resolved through negotiation and the establishment of alliances, showing how being audited requires complex political skills.